Profil Kepemimpinan Pembelajaran Kepala Sekolah di Sekolah Dasar - Supriyadi, Supriyadi; Khairani, Fadhilah; Riswandi, Riswandi; Nursidik, Imay (JURNAL MANAJEMEN MUTU PENDIDIKAN, 2023)
This study aims to describe and explain the learning leadership of talk, walk and be the caddy principals. This type of research was qualitative with a descriptive method and character it is natural because the object that is developed as it is not manipulated and the presence of the author has no effect on the object. Retrieval of data sources by means of purpose sampling and snowball sampling. The research subjects were principals, school committees, educators, staff, parents of students and students. The object of the research is a descriptive study of the principal’s learning leadership in developing learning leadership. Data collection techniques using observation, documentation and interviews. The research instrument used observation sheets, documentation and interview guidelines. Data analysis techniques from collecting data, raw data description, data reduction, data categories and relationships between categories. Test the validity of the data using credibility, transferability, dependability, and confirmability tests. Based on the results of research on the profile of principals’ learning leadership in elementary schools, it has been well establishedKeywords: Learning leadership talk, walk and be the caddy, Principal.DOI: 10.23960/jmmp .v11.i2.2023.01